2011
DOI: 10.4172/jbb.1000076
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism Studies of Desvenlafaxine

Abstract: Background: This series of experiments was conducted to describe the metabolic profile of the serotoninnorepinephrine reuptake inhibitor desvenlafaxine (administered as desvenlafaxine succinate) using animal and human models. Methods: In vivo and in vitro experiments were conducted with humans and preclinical species (CD-1 mice, Sprague Dawley rats, and beagle dogs). Single oral doses of [ 14 C]-desvenlafaxine were administered to each preclinical species for analyses of desvenlafaxine concentration in plasma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…One hour after DVS administration the animals were given ALA (100 or 200 mg/ kg). The time interval between the administration of DVS and ALA was set at 1 h because a previous study showed that the maximum mean plasma concentration of DVS in mice occurred 1 h after oral administration of the drug (DeMaio et al, 2011). The experimental design is represented in Fig.…”
Section: Treatment Groupsmentioning
confidence: 99%
“…One hour after DVS administration the animals were given ALA (100 or 200 mg/ kg). The time interval between the administration of DVS and ALA was set at 1 h because a previous study showed that the maximum mean plasma concentration of DVS in mice occurred 1 h after oral administration of the drug (DeMaio et al, 2011). The experimental design is represented in Fig.…”
Section: Treatment Groupsmentioning
confidence: 99%
“…In a single study involving telaprevir, escitalopram area under the curve (AUC) was reduced by 35%, suggesting the need for clinicians to monitor the need for dose optimization on triple therapy [50]. No significant DDI has been observed between escitalopram and boceprevir [37].…”
Section: Resultsmentioning
confidence: 99%
“…Primeiro, as vias de administração foram diferentes (desvenlafaxina -administração oral; dimenidrinato -administração intravenosa). Segundo, a principal via de metabolização da desvenlafaxina é a glucorunização e, em menor extensão, a via oxidativa da isoforma do citocronomo P450 3A4 (DeMaio et al, 2011;Spina et al, 2012)2012, enquanto o metabolismo do dimenidrinato envolve a isoforma CYP2D6 (Takeda, 2009).…”
Section: Desenho Experimentalunclassified
“…Sobre o metabolismo da desvenlafaxina, a principal via envolvida é a glucuronidação através da UDP-glucuroniltransferase (isoformas UGT1A1, UGT1A3, UGT2B4, UGT2B15 e UGT2B17) e, em menor extensão, através do metabolismo oxidativo (N-desmetilação) pela isoforma do citocromo P450 3A4 (CYP3A4) (DeMaio et al, 2011). Devido a essas características no metabolismo, a desvenlafaxina apresenta vantagens em relação a outros antidepressivos como a venlafaxina (metabolizada extensivamente pela isoforma CYP2D6), pois a interação com outros fármacos é reduzida ou inexistente (Colvard, 2014)"container-title":"Mental Health Clinician","page":"35-39","volume":"4","issue":"1","source":"mhc.cpnp.org (Atypon.…”
Section: Introductionunclassified